"Shut up and dribble!"?Athletes activism in the age of twittersphere: The case of LeBron James. (August 2019) - Galily, Yair
Abstract: As many sport scholars claimed before, sport does not operate in isolation from broader society. Instead, sport serves as a site where societal inequalities such as racism, sexism, economic stratification, and other forms of oppression are reproduced, exacerbated, and/or ignored. Thus, the aim of the current paper is to look chronologically and conceptually at the way in which LeBron James's activism is altering not only the sporting realm but more importantly, the political discourse. In times of political polarization, when exposure to cross-cutting discourse is missing, people are far less likely to perceive opposing standpoints as legitimate, and less able to provide rational explanation to their own political decisions. LeBron's activism leveraging his position as one the world's most followed sportsperson, to assume awareness is an interesting phenomenon worth reviewing. In that respect, the Lebron case is remarkable. Only few figures can reach the other side of the political passageway and James, who's probably the most famous athlete in the US if not the world, is one of the only people whose words have a chance to resound with the people as a whole. It is argued here that the ability of high-profile athletes who openly identify with one side of the political map to attract not only fans whose opinions they reinforce but also those who belong to the other side of the political map, thus contributing towards bursting the current online echo-chamber. Highlights: The aim of the current paper was to look chronologically and conceptually at the way in which LeBron James's activism is altering not only the sporting realm but more importantly, the political discourse. In times of political polarization, when exposure to cross-cutting discourse is missing, people are far less likely to perceive opposing standpoints as legitimate, and less able to provide rational explanation to their own political decisions. It is argued here that the ability of high-profile athletes who openly identify with one side of the political map to attract not only fans whose opinions they reinforce but also those who belong to the other side of the political map, thus contributing towards bursting the current online echo-chamber.